Strategi Pemasaran Digital Usaha Mikro, Kecil, Dan Menengah Di Desa Batu Makap Kabupaten Murung Raya - Dicky Perwira Ompusunggu; Dicky Febrian (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to contribute knowledge about Indonesian consumer behavior and marketing strategies through social media that can help businesses increase their product sales in the increasingly competitive Murung Raya district market. A qualitative research method was used in this study. The research location is the Batu Makap Industrial Tourism Village in Murung Raya Regency. In Batu Makap village, researchers conducted structured interviews with respondents from SMEs and digital village managers. The existence of this information technology has an impact on existing markets and existing business agreements. Steps will be taken to introduce SMEs to digital marketing and attract them to participate in loan programs to use digital marketing techniques. In addition, MSME players will also learn about marketing strategies such as digital marketing, online shopping, and product development. Digital marketing enables marketing and selling products based on customer location. Some MSMEs have mastered using technology to sell their products. In developing a digital village in Makapu Village, Murung Raya District, digital marketing has enabled MSMEs to lead their marketing. Steps have been taken to introduce MSMEs to digital marketing and encourage them to participate in lending programs and use digital marketing techniques.